Plasmapheresis as a Promising Therapeutic Option to TreatMacrophage Activation Syndrome - Bansal Varun (Indonesian Rheumatology Associantion, 2024)
Macrophage activation syndrome (MAS) is a lethal complication ofautoimmune conditions. Its diagnosis and management remainschallenging till date in view of paucity of standard protocols.Plasmapheresis has shown promise if used early in the course ofdisease. We hereby describe a case report of a young male patient whopresented with multiorgan failure. He was diagnosed with MAStriggered by systemic lupus erythematosus (SLE). He was successfullytreated with steroids, cyclophosphamide and plasmapheresis.